Examining water diffusion through phospholipids by molecular dynamics - Ducut, Melsa Rose D. (Animo Repository, 2015)
Biodiesel is a carbon neutral renewable source of energy which can be an alternative to fossil fuel. One potential source of biodiesel which is recently being studied is microalgae. Microalgae are composed of lipids which can be processed into biodiesel. However, one of the primary concerns regarding the commercialization and production of microalgal biofuel is the drying process. A search for a new drying method that is less energy intensive is needed to make microalgal biodiesel viable. On this regard, we opted to model the drying process of microalgae using molecular dynamics. The objective of this study is to investigate the effects of varying the temperature and pressure on the mechanism of extracting water from a lipid bilayer composed of 32 dilauroylphosphatidylcholine (DLPC) lipids, 32 dioleolyphosphatidylcholine (DOPC) lipids, 32 dipalmitoylphosphatidylcholine (DPPC) lipids, 32 distearoylphosphatidylcholine (DSPC) lipids and 6000 water molecules in an all-atom force field. The lipid bilayer was modelled using GROMACS (GROningen MAchine for Chemical Simulations) and VMD (Visual Molecular Dynamics) software. The system was equilibrated at 300 K temperature and 1 bar pressure for 100 ns. The temperature was varied from 300 K to 370 K with 10 K interval. The pressure was varied from 7.50 MPa to 13.50 MPa with 2 MPa interval to investigate the effect of increasing the pressure on the migration of water through the lipid bilayer. Results showed that increased temperature increased the bilayer thickness. Furthermore, an increase in pressure resulted to a decrease in the time it took for the water to migrate through the lipid bilayer.